DISSOLUTION AND MINERALIZATION CHARACTERIZATION OF BIOACTIVE GLASS CERAMIC CONTAINING ENDODONTIC SEALER GUTTAFLOW BIOSEAL - Hoikkala, Niko (My University, 2019)
Aim of the study was to evaluate apatite-forming ability and ion dissolution of bioactive glass-ceramic (BGC) particles from novel polydimethylsiloxane (PDMS) based endodontic sealer Guttaflow Bioseal. Firstly, water sorption and solubility were determined for Guttaflow 2 and Guttaflow Bioseal (GB), the latter containing BGC filler particles. Mineral precipitations in simulated body fluid (SBF) were observed with SEM/EDX. Ion-release from the sealer was determined with inductively coupled plasma optical emission spectrometry (ICP-OES) in Tris-buffer solution. Change of pH was measured also after 14 days. The obtained data was statistically analyzed with Tukey’s HSD test (p<0.05). GB exhibited significantly higher water sorption and solubility in comparison with Guttaflow 2. Surface structure exposed particles of BGC in the PDMS matrix. The BGC particles (size of 20–40 μm) indicated to consist of CaO-SiO2-Na2O-ZrO2-P2O5. Morphologically spherical Ca/P precipitation formed after 3 days in the SBF on the sealer surface. Ca/P ratio of the precipitation ranged in 1.20–1.65 indicating transformation to hydroxyapatite (HA). The pH of the immersion solution rose gradually.
Keywords: Bioactive glass-ceramic, Endodontic sealer, Guttaflow Bioseal, Ion-release, Apatite-forming ability